State Eligibility Test (SET), Tamil Nadu: A Five Point Scaling Analysis of the Result of 2011 - Mandhirasalam, M.; Srinivasa Ragavan, S. (Journal of Information and Knowledge, 2015)
This paper is an overview of State Eligibility Test (SET), Tamil Nadu which determines the eligibility of candidates for recruitment of assistant professors in colleges and universities in Tamil Nadu and Pondicherry and analyses its results of 2011. The paper briefly discusses about NET and SET, its structure, selection criteria and discusses elaborately about the results of the 2011 session using five point scaling analysis ie. very good, good, medium, poor and very poor on the pass percentage. At the end, major findings of the study and some suggestions to increase the number of awardees of NET/SET are also given.